REGIONAL REGULATION CONCERNING WASTE MANAGEMENT IN KUTA, BADUNG TECHNICAL SERVICE UNIT - Nyoman Diah Utari Dewi (DIA: Jurnal Administrasi Publik, 2020)
Implementation of Badung Regency Regional Regulation No. 7 of 2013 concerning Waste Management is an effort to find out about the policies implemented by the Badung Regency Government for waste management, especially in the Kuta area. This research is a qualitative research in which data is obtained from area observations, interviews, documentation and library research as well as online searches, systematically described in accordance with the formulation of the problem of implementing Regional Regulations and finding obstacles and solutions implemented in waste management in the Service Unit Kuta Technical, analyzed using the Merilee Implementation Model from S. Grindle, namely content of policy and context implementation. The results of an analysis of the Implementation of the Badung District Regulation No. 7 of 2013 concerning Waste Management in the Kuta Technical Services Unit, found weaknesses in the implementation of the Local Regulation policy and several obstacles encountered including the low willingness of the community to sort out their own garbage and often violate the disposal schedule rubbish, adding transportation facilities and infrastructure as well as the existence of Temporary Shelter in each Village / Kelurahan, and the involvement of Indigenous Villages in waste management by incorporating it into set of rules made by and for residents of a village and it’s called Awig-awig.